ISLAMIC CULTURE MODEL AS THE MAIN PREDICTOR OF OPTIMIZING ZAKAT FUND MANAGEMENT - Sismanto, Sismanto; Chandraningtyas, Iva; Andriani, Sri; Huda, Achmad Miftachul (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 8 No 1 (2022): The 8th International Conference Of Islamic Economics And Business (ICONIES 2022), 2022)
This article presents a conceptual model for optimizing the absorption of zakat funds in BAZNAS. Islamic culture is an important study in the conceptual framework that will be discussed in this article, in which this culture will involve culture in each target area. The main objective of optimizing the absorption of zakat funds is, of course, to improve the protection of the socio-economic conditions of the poor. This article uses a literature study approach by collecting data from the relevant scientific literature. Results: This article identifies the right method to optimize the absorption of zakat funds in Baznas. This optimization becomes very important considering that zakat can function as a solution for the socio-economic welfare of the wider community. Conclusion and suggestions: The conceptual model in this article includes the variable of Islamic culture as the main predictor of the ideas that have been built. The discussion strengthens the researcher's argument for using a cultural approach to optimizing the absorption of zakat funds in the regions. This article presents a conceptual model that can be a consideration for Basnaz in optimizing zakat funds and being useful for further empirical research in the scope of optimizing zakat funds. This article only presents a conceptual framework. Therefore the researcher does not include empirical validation of the ideas the researcher has built. That is why further research is needed to validate the conceptual model presented in this article. The discussion strengthens the researcher's argument for using a cultural approach to optimizing the absorption of zakat funds in the regions.